Association Between Psychotic Experiences and Subsequent Suicidal Thoughts and Behaviors - World Health Organization World Mental Health Survey Collaborators (2017)
Importance: Community-based studies have linked psychotic experiences (PEs) with increased risks of suicidal thoughts and behaviors (STBs). However, it is not known if these associations vary across the life course or if mental disorders contribute to these associations. Objective: To examine the temporal association between PEs and subsequent STBs across the life span as well as the influence of mental disorders (antecedent to the STBs) on these associations. Design, Setting, and Participants: A total of 33 370 adult respondents across 19 countries from the World Health Organization World Mental Health Surveys were assessed for PEs, STBs (ie, ideation, plans, and attempts), and 21 DSM-IV mental disorders. Discrete-time survival analysis was used to investigate the associations of PEs with subsequent onset of STBs. Main Outcomes and Measures: Prevalence and frequency of STBs with PEs, and odds ratios and 95% CIs. Results: Of 33 370 included participants, among those with PEs (n = 2488), the lifetime prevalence (SE) of suicidal ideation, plans, and attempts was 28.5% (1.3), 10.8% (0.7), and 10.2% (0.7), respectively. Respondents with 1 or more PEs had 2-fold increased odds of subsequent STBs after adjusting for antecedent or intervening mental disorders (suicidal ideation: odds ratio, 2.2; 95% CI, 1.8-2.6; suicide plans: odds ratio, 2.1; 95% CI, 1.7-2.6; and suicide attempts: odds ratio, 1.9; 95% CI, 1.5-2.5). There were significant dose-response relationships of number of PE types with subsequent STBs that persisted after adjustment for mental disorders. Although PEs were significant predictors of subsequent STB onset across all life stages, associations were strongest in individuals 12 years and younger. After adjustment for antecedent mental disorders, the overall population attributable risk proportions for lifetime suicidal ideation, plans, and attempts associated with temporally prior PEs were 5.3%, 5.7%, and 4.8%, respectively. Conclusions and Relevance: Psychotic experiences are associated with elevated odds of subsequent STBs across the life course that cannot be explained by antecedent mental disorders. These results highlight the importance of including information about PEs in screening instruments designed to predict STBs.